Prognostic value of blood cell count-derived ratios in BRAF-mutated metastatic melanoma - Kopecky, Jindrich; Kubecek, Ondrej; Priester, Peter; Vosmikova, Hana; Cermakova, Eva; Kyllarova, Aneta (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
BACKGROUND: The treatment and prognosis of metastatic melanoma have changed during the last decade to include immunotherapy or targeted therapy as standard therapeutic options for BRAF-mutated melanoma. However, predictive and/or prognostic markers are lacking, especially in clinical situations where several options are available. The aim of this study was to determine the association of pre-therapeutic blood cell count-derived ratios (BCDR) with survival in patients with BRAF-mutated metastatic melanoma. METHODS: We evaluated the prognostic role of BCDR in therapy-naïve patients with BRAF-mutated metastatic melanoma treated with immune checkpoint inhibitors or targeted therapy. The impact of BCDR on survival was analysed using univariate and multivariate Cox proportional hazard models. RESULTS: We enrolled 46 patients treated with BRAF inhibitors and 20 patients who received anti-PD-1 checkpoint inhibitors. The median progression-free survival (PFS) and overall survival (OS) were 8.3 and 18.2 months, respectively, with no statistical difference between groups. The objective response rate was 39% (30% in the anti-PD-1 and 44% in the targeted therapy groups). Baseline BCDR values were associated with improved PFS and OS in the immunotherapy group. Only the platelet-to-lymphocyte ratio (PLR) was associated with OS and PFS in the targeted therapy group. Independent prognostic indicators for PFS were lactate dehydrogenase, PLR and the lymphocyte-to-monocyte ratio (LMR) and those for OS were LMR, toxicity and the number of initial metastases. CONCLUSION: BCDR had a substantial prognostic value in patients with BRAF-mutated metastatic melanoma treated with immune checkpoint inhibitors. However, a prognostic role for BCDR seemed less apparent in patients treated with targeted therapies.
Keywords: targeted therapy; melanoma; prognostic factors; Blood Cell Count; Prognosis; retrospektivní studie; protoonkogenní proteiny B-Raf; inhibitory kontrolních bodů; krevní obraz; Humans; immunotherapy; lidé; Retrospective Studies; Melanoma; Immune Checkpoint Inhibitors; Proto-Oncogene Proteins B-raf; prognóza; melanom